2014
DOI: 10.9790/3013-0405068074
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the implementation of Pharmaceutical Care into the UAE community pharmacies

Abstract: :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
2
0
2
Order By: Relevance
“…These findings are correlated because if the hospital does not have enough staffing, staff members will be overworked and have limited time to engage in professional development activities that will help them acquire more knowledge on therapeutics. The results in this study are compatible to those found by Ghazal and colleagues, as they reported lack of time, insufficient staffing and lack of motivation or vision of professional development to be the http://www.hsag.org.za Open Access main barriers to the implementation of pharmaceutical care into pharmacies (Ghazal et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are correlated because if the hospital does not have enough staffing, staff members will be overworked and have limited time to engage in professional development activities that will help them acquire more knowledge on therapeutics. The results in this study are compatible to those found by Ghazal and colleagues, as they reported lack of time, insufficient staffing and lack of motivation or vision of professional development to be the http://www.hsag.org.za Open Access main barriers to the implementation of pharmaceutical care into pharmacies (Ghazal et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…It is not uncommon to see only one pharmacist present at a community pharmacy at any given time, which explains why a number of studies have highlighted the same barriers to providing pharmaceutical care as our participants, such as limited time, the lack of trained personnel, and the lack of motivation 3941. Previously, provisionally registered pharmacists (PRP) in Malaysia were only allowed to do their one-year training in the government setting.…”
Section: Discussionmentioning
confidence: 97%
“…This need for access to comprehensive patient information has been highlighted in previous studies examining pharmacy services, both in England 54 and internationally. 55 , 56 , 57 , 58 , 59 …”
Section: Discussionmentioning
confidence: 99%